Pengaruh Fermentasi L. Plantarum dan Medium Roast terhadap Profil Sensorik Metode Cupping pada Kopi Arabika Var. Lini S - Lenny Amelia HK; Kelik Putranto (Ma'soem University, 2026)
The potential of Lini S Arabica coffee, known for its sweet base flavor and floral nuances, is often not fully realized due to conventional post-harvest processing. This study aimed to analyze the influence of controlled fermentation using Lactobacillus plantarum combined with a medium roast profile on the sensory quality of Lini S variety brewed coffee. The research employed an experimental design with two treatment groups: a control group (C) undergoing natural fermentation and a treatment group (F) inoculated with L. plantarum. Both groups were then roasted using a medium roast profile (final temperature of 205°C). Sensory analysis was conducted using the SCAA cupping method by three trained panelists. The obtained data were tested statistically using an independent t-test at a 5% significance level (? = 0.05). This research conclusively demonstrates that the controlled fermentation treatment using the bacterium Lactobacillus plantarum combined with a medium roast significantly improved the sensory quality of Arabica coffee, Lini S variety, compared to natural fermentation (control). The SCAA cupping scores reinforce this finding, where the treatment group (F) inoculated with L. plantarum obtained a significantly higher total score (86.25) compared to the control group (C) (78.75). This score improvement was observed across all sensory attributes. The highest score increases were seen in the attributes of flavor (from 7.25 to 8.50), acidity (from 7.00 to 8.50), and balance (from 7.00 to 8.50). The study concludes that the effect of L. plantarum fermentation combined with a medium roast is a viable method for enhancing the sensory quality and commercial value of Arabica Lini S coffee.